2001
DOI: 10.2165/00007256-200131010-00002
|View full text |Cite
|
Sign up to set email alerts
|

Interval Training for Performance: A Scientific and Empirical Practice

Abstract: This article traces the history of scientific and empirical interval training. Scientific research has shed some light on the choice of intensity, work duration and rest periods in so-called 'interval training'. Interval training involves repeated short to long bouts of rather high intensity exercise (equal or superior to maximal lactate steady-state velocity) interspersed with recovery periods (light exercise or rest). Interval training was first described by Reindell and Roskamm and was popularised in the 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
171
2
14

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 433 publications
(193 citation statements)
references
References 68 publications
6
171
2
14
Order By: Relevance
“…The recovery between the three sets was passive and lasted 5 min. The choice of three sets was in line with previous studies demonstrating that T lim can be sustained two to three times in the same IT session (Billat 2001). Moreover, this is a common training practice in the track and field area.…”
Section: Intermittent Running Sessionssupporting
confidence: 64%
See 2 more Smart Citations
“…The recovery between the three sets was passive and lasted 5 min. The choice of three sets was in line with previous studies demonstrating that T lim can be sustained two to three times in the same IT session (Billat 2001). Moreover, this is a common training practice in the track and field area.…”
Section: Intermittent Running Sessionssupporting
confidence: 64%
“…CV were calculated by the means of the boostrap method indicating the variability associated with the modelling procedure (Robinson et al 1991). It was also reported that the main criteria in IT efficiency are the percentage of _ V V O 2max and the time for which it is sustained (Billat 2001;Robinson et al 1991;Tabata et al 1997). Nevertheless, although IT 105% is a more effective method for sustaining a greater duration near _ V V O 2max in athletes with slow _ V V O 2 kinetics, its effectiveness in improving _ V V O 2max would require a longitudinal study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aiming to demonstrate the validity as well as the ability of the model [24] to simulate heart rate kinetics, the following different intensity patterns were selected, as examples: 1. incremental exercise, strictly increasing velocity, 2. incremental exercise, sequence of steps, 3. interval training [4,5].…”
Section: Intensity Pattern Simulationmentioning
confidence: 99%
“…The simulated interval training pattern follows the recommendations presented in [4] and [5]. Let us assume that the velocity pattern consists of a sequence of N sets of exercise intervals and their subsequent recoveries.…”
Section: Interval Trainingmentioning
confidence: 99%